A model-based approach for strategy planning of collaborative humanoid soccer robot / Norheliena Aziz - Aziz, Norheliena (2015)
Collaborative multi-robot system has drawn a great attention in the past decades. With recent advances in hardware and software, such system has become more versatile and applicable in various fields. One of the best research platforms for research in multi robot system is robotic soccer and the most known event promoting robotic soccer is RoboCup. In RoboCup, Standard Platform League (SPL) requires all participants to use the same hardware which is NAO humanoid robot with no modification allowed. Therefore, winning chance is fully depended on the software development of the team. Many teams have developed a more or less operative system with locomotion and image processing capabilities. However, most of the teams still do not take the advantage of collaboration between players. Because of the increasing size of teams, team coordination will be the distinctive factor in the success of a team in the coming years. In order to design a system with good coordination, it requires operation robustness, behavior optimality under dynamic environments, and agility in order to response to any changes. The development of such system is a challenge, especially during the conceptual design phase. Therefore, the aim of this study is to presents a model-based approach for strategy planning of humanoid soccer robot team based on a principal solution which defines the coordination concepts for the collaborative robotic soccer players. The principal solution is the foundation of the first analysis, verification and validation on the system level. In order to construct the requirements of such system, a specification technique is designed in order to describe the principal solution. Therefore, all the aspects needed has been identified such functions, environments, active structure, behavior and application scenarios. These aspects are represented by partial models which related to each other, thus creating a principal solution. To ensure effective communication during the process, a specification technique called “Conceptual Design Specification Technique for the Engineering of Complex Systems (CONSENS) has been applied. By using this method, a strategy for collaborative humanoid robot soccer has been proposed. Such model provides a lucid interface and also facilitates the development process whether for simulation or field test. Furthermore, it was designed to ease any modification since the structure has been organized into several parts.